Perceived discrimination in fatigue: a qualitative interview study in the SOMA.SOC project - Barbek, Rieke; Makowski, Anna Christin; von dem Knesebeck, Olaf (Frontiers in Sociology, 2025)
IntroductionFatigue is a frequent somatic symptom impacting health and well-being and lately receiving increased attention as a long-term consequence of COVID-19. Emerging evidence suggests that persons afflicted with fatigue symptoms are often stigmatized and discriminated because their symptoms are still poorly understood and not recognizable to others. Existing stigma research mainly focused on specific medical conditions and domains and overlooked intersectional discrimination – the negative amplification effect of intersecting social identities. The purpose of the current study is to examine perceived discrimination in fatigue across different medical conditions and domains, also considering intersectional discrimination.Materials and methodsSemi-structured telephone interviews were carried out with 19 patients with clinically significant fatigue, considering a variety of different social identities like gender, history of migration, and occupational status. The interviews were analyzed using a structured qualitative content approach with consensual coding.ResultsThe findings on perceived discrimination could be subsumed in eight practices: (nonverbal) communication, negative emotional reaction, medical treatment, leadership responsibility, structural barriers, diagnostic terminology, and scientific controversy. Participants reported overlapping experiences of perceived discrimination across several intertwined domains: medical setting, work, social, public, and at an overarching structural level. Thereby, especially discrimination in the medical setting and on structural level occurred with great impact on health care and social protection. By applying an intersectional approach, intersectional discrimination specific for certain stigmatized social identities, like female gender and low occupational status became apparent.DiscussionThese findings need to be further researched and addressed in intervention strategies increasing resilience and public knowledge to reduce intersectional discrimination and health inequalities.